Sound and Music Computing - Meinard Müller (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Sound and music computing is a young and highly multidisciplinary research field. It combines scientific, technological, and artistic methods to produce, model, and understand audio and sonic arts with the help of computers. Sound and music computing borrows methods from computer science, electrical engineering, mathematics, musicology, and psychology.